Pengetahuan Siswa Tentang Metamorfosis: Metode Ceramah Vs Metode Diskusi Pada Strategi Pembelajaran Dan Motivasi Belajar - NDOLUANAK, YOFRAN HENGKI; Rahayu, Wardani; Riyadi, Riyadi (Jurnal Evaluasi Pendidikan, 2023)
This research aims to evaluate the effectiveness of the lecture method and discussion method in influencing students' knowledge about metamorphosis, as well as their impact on learning strategies and learning motivation. The research sample consisted of class VII students who were divided into two groups: the first group was taught using the lecture method, while the second group was taught using the discussion method. Experimental design research method. The results showed that the group taught using the discussion method obtained significantly higher scores than the lecture group, indicating a better increase in knowledge about metamorphosis. In addition, students in the discussion group showed more effective learning strategies and higher learning motivation than the lecture group. These findings emphasize the importance of learning methods that involve active student participation, such as discussions, in increasing students' mastery of concepts, learning strategies, and motivation to learn about the topic of metamorphosis.